The Effect of Co-infection of Food-Borne Pathogenic Bacteria on the Progression of Campylobacter jejuni Infection in Mice - Wang, Gang; He, Yufeng; Jin, Xing; Zhou, Yonghua; Chen, Xiaohua; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Frontiers in Microbiology, 2018)
Campylobacter is a well-known food-borne pathogen that causes human gastroenteritis. Food products that contain Campylobacter may also be contaminated by other pathogens; however, whether this multiple contamination leads to more severe infection remains unclear. In this study, mice were gavaged with Campylobacter jejuni and other food-borne pathogenic bacteria to mimic a multiple infection. It was demonstrated that the Campylobacter jejuni load was elevated when the mice were co-infected with C. jejuni and Salmonella typhimurium, and the campylobacteriosis that followed was also enhanced, with features of decreased body weight, heavier bloody stools and more pronounced inflammatory changes to the colon. In addition, infection with C. jejuni was also promoted by co-infection with entero-invasive Escherichia coli but unaffected over time. In contrast to S. typhimurium and entero-invasive E. coli, co-infection by Listeria monocytogenes showed little effect on C. jejuni infection and even hindered its progress. In addition, the intestinal microecology was also affected by co-infection of C. jejuni with other pathogens, with an increased relative abundance of unclassified Enterobacteriaceae, decreased levels of butyric acid and changes in the abundance of several genera of gut microbe, which suggests that some food-borne pathogenic bacteria might affect the progression of C. jejuni infection in mice by influencing the composition of the gut microbiota and the resulting changes in SCFA levels. Collectively, our findings suggest that co-infection of Campylobacter with other pathogenic bacteria can impact on the progression of infection by C. jejuni in mice, which may also have implication for the aetiology of Campylobacter on human health.